Gamma-gamma prime-gamma double prime dual-superlattice superalloys. (15th July 2017) - Mignanelli, P.M.; Jones, N.G.; Pickering, E.J.; Messé, O.M.D.M.; Rae, C.M.F.; Hardy, M.C.; Stone, H.J.
Abstract: Improving the efficiency of gas turbine engines requires the development of new materials capable of operating at higher temperatures and stresses. Here, we report on a new polycrystalline nickel-base superalloy that has exceptional strength and thermal stability. These properties have been achieved through a four-element composition that can form both gamma prime and gamma double prime precipitates in comparable volume fractions, creating an unusual dual-superlattice microstructure. Alloying studies have shown that further property improvements can be achieved, and that with development such alloys may be suitable for future engine applications. Graphical abstract: